Impact of increased horizontal resolution in coupled and atmosphere-only models of the HadGEM1 family upon the climate patterns of South America - Custodio, Maria de Souza [UNESP]; Rocha, Rosmeri Porfirio da; Ambrizzi, Tercio; Vidale, Pier Luigi; Demory, Marie-Estelle (Springer, 2017)
This study investigates the impact of increased horizontal resolution in coupled and atmosphere-only global climate models on the simulation of climate patterns in South America (SA). We analyze simulations of the HadGEM1 model family with three different horizontal resolutions in the atmosphere-N96 (similar to 135 km at 50A degrees N), N144 (similar to 90 km) and N216 (similar to 60 km)-and two different resolutions in the ocean-1A degrees and 1/3A degrees. In general, the coupled simulation with the highest resolution (60 km in the atmosphere and 1/3A degrees in the ocean) has smaller systematic errors in seasonal mean precipitation, temperature and circulation over SA than the atmosphere-only model at all resolutions. The models, both coupled and atmosphere-only, properly simulate spatial patterns of the seasonal shift of the Intertropical Convergence Zone (ITCZ), the formation and positioning of the South Atlantic Convergence Zone (SACZ), and the subtropical Atlantic and Pacific highs. However, the models overestimate rainfall, especially in the ITCZ and over the western border of high-elevation areas such as southern Chile. The coupling, combined with higher resolution, result in a more realistic spatial pattern of rain, particularly over the Atlantic ITCZ and the continental branch of the SACZ. All models correctly simulate the phase and amplitude of the annual cycle of precipitation and air temperature over most of South America. The overall results show that despite some problems, increasing the resolution in the HadGEM1 model family results in a more realistic representation of climate patterns over South America and the adjacent oceans.
Keywords: South America; Coupled; Atmospheric; Resolution